Diffuse Institutional Trust and Specific Institutional Mistrust in Nordic Participatory Planning: Experience from Contested Urban Projects. (15th March 2019) - Lehtonen, Markku; De Carlo, Laurence
ABSTRACT: Trust is vital in participatory planning. To explore the complex relationships between participation and various dimensions of trust and mistrust, this article develops a framework of analysis distinguishing between specific and diffuse forms of institutional trust and mistrust, and illustrates its relevance via two case studies of urban and transport planning in Finland and Sweden. We explore the dynamic coexistence of mistrust towards the specific planning organisations in charge of the projects with the strong 'diffuse' trust in the generic institutions of representative democracy and Nordic planning. The proposed approach can help harness mistrustful civic vigilance for deliberative purposes.